THE ROLE OF DIGITAL ECONOMY IN SOCIAL LIFE - Amridinova, Dilrabo Tursunovna; Yo‘ldosheva , Bahoroy Nurmat qizi (Educational Research in Universal Sciences, 2023)
In the article, a key aspect is the definition of conditions and factors affecting the accelerated development of the digital economy in our country. The essence of the digital economy is studied as a new type of economy that changes the format of government, education, health care, communication between people and sets a new paradigm for the development of the state, the economy and the whole society. It emphasizes the relevance of training qualified management personnel to perform various types of work in the digital segment of the economy, and in this regard, a fundamental change in the concept of education. The necessity of the processes of continuous learning and the development of professional training and retraining, the acquisition of new competencies and advanced training of employees of modern organizations has been substantiated.